If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 40)(4x + -20) = 0 Reorder the terms: (40 + 5x)(4x + -20) = 0 Reorder the terms: (40 + 5x)(-20 + 4x) = 0 Multiply (40 + 5x) * (-20 + 4x) (40(-20 + 4x) + 5x * (-20 + 4x)) = 0 ((-20 * 40 + 4x * 40) + 5x * (-20 + 4x)) = 0 ((-800 + 160x) + 5x * (-20 + 4x)) = 0 (-800 + 160x + (-20 * 5x + 4x * 5x)) = 0 (-800 + 160x + (-100x + 20x2)) = 0 Combine like terms: 160x + -100x = 60x (-800 + 60x + 20x2) = 0 Solving -800 + 60x + 20x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '20'. 20(-40 + 3x + x2) = 0 Factor a trinomial. 20((-8 + -1x)(5 + -1x)) = 0 Ignore the factor 20.Subproblem 1
Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-8, 5}
| 8/5(x)=24 | | -2=(x-100)/15 | | 10x-2=5x+3 | | 2w^2=8 | | 18x=138 | | 8x+4(1.5x)=115.38 | | ((-x/y)1/3)6) | | 8x+4(1.5x)=11.38 | | 2=(x-100)/15 | | -y+12=47 | | 0.76(8b+4)-2=4b+14 | | 6t+5=55 | | 8x+4(1.5x)=116 | | 4/(3w)=x/(9w^9) | | 2n-3=0 | | 3v+s=S+2v+v | | 6x-0=-14 | | 4/3w=x/9w^9 | | -4=1/4x | | y-4y+3y=0 | | E^2x+1=13 | | 65/7 | | 40-2p=p-5 | | 6/5/7 | | x^2+kx-4=-k+x+1f | | 40-2p=-5+p | | 3x+4x=27 | | 2x+7=x+x+7 | | 2x+4x+18=25 | | X+3+3=7+4 | | 7x+2=4x+x+1+2x+1 | | (-8-3)-5(2-5)= |